Taking the pulse of the outer Milky Way with the Halo Outskirts With Variable Stars (HOWVAST) survey: an RR Lyrae density profile out to >200 kpc - Medina, Gustavo E.; Muñoz, Ricardo R; Carlin, Jeffrey L; Vivas, A Katherina; Grebel, Eva K.; Martínez-Vázquez, Clara E; Hansen, Camilla J (Monthly notices of the Royal Astronomical Society, 2024)
In order to constrain the evolutionary history of the Milky Way, we hunt for faint RR Lyrae stars (RRLs) using Dark Energy Camera data from the High cadence Transient Survey and the Halo Outskirts With Variable Stars survey. We report the detection of $\sim$500 RRLs, including previously identified stars and $\sim$90 RRLs not yet reported. We identify nine new RRLs beyond 100 kpc from the Sun, most of which are classified as fundamental-mode pulsators. The periods and amplitudes of the distant RRLs do not place them in either one of the two classical Oosterhoff groups, but in the Oosterhoff intermediate region. We detect two groups of clumped distant RRLs with similar distances and equatorial coordinates, which we interpret as an indication of their association with undiscovered bound or unbound satellites. We study the halo density profile using spheroidal and ellipsoidal ($q=0.7$) models, following a Markov chain Monte Carlo methodology. For a spheroidal halo, our derived radial profile is consistent with a broken power law with a break at $18.1^{+2.1}_{-1.1}$ kpc separating the inner and the outer halo, and an outer slope of $-4.47^{+0.11}_{-0.18}$. For an ellipsoidal halo, the break is located at $24.3^{+2.6}_{-3.2}$ kpc and the outer slope is $-4.57^{+0.17}_{-0.25}$. The break in the density profile is a feature visible in different directions of the halo. The similarity of these radial distributions with previous values reported in the literature seems to depend on the regions of the sky surveyed (direction and total area) and halo tracer used. Our findings are compatible with simulations and observations that predict that the outer regions of Milky Way-like galaxies are mainly composed of accreted material.